Dating of Hadith About Riba; The Reflection Theory of Isnad Cum Matn Analyzed by Harald Motzki: Dating Hadis Tentang Riba; Refleksi Teori Isnad Cum Matn Analysis Harald Motzki - Arif Budiman; Fathul Mu'in; Qurrota A'yun (Takwil: Journal of Quran and Hadith Studies, 2022)
This article aims to demonstrate Harald Motzki's theory of isnad-cum-matn analysis by tracing the hadith about usury. This hadith research theory is based on the historical critical approach (HCA) which is commonly used by Western scholars in investigating the validity of a hadith. This hadith dating method is carried out through an analysis of hadith transmission based on the simultaneous isnād and matan analysis methods. The main reference in tracing the origin of this hadith is by analyzing the pathways of transmission (isnad) by collecting and comparing variations of hadith texts, detecting partial common links (pcl) and common links (cl) in different paths of transmission and examining the material for find the common link whether purely as the first collector of the hadith. The author's findings in theoretical reflection on the hadith about usury show the Prophet SAW as a common link with three companions as partial common links, namely Abdullah Ibn Mas'ud, Abu Hurairah and Bara' Ibn Hazib.